2020
DOI: 10.1002/hast.1081
|View full text |Cite
|
Sign up to set email alerts
|

Trust in American Medicine: A Call to Action for Health Care Professionals

Abstract: Medical mistrust has a well‐documented harmful impact on a range of patients’ health behaviors and outcomes. It can have such egregious downstream effects on so many aspects of medicine—from clinical trial participation to health care use, timely screening, organ donation, and treatment adherence—that it is sometimes described as one of the social determinants of health. In the article “Trust, Risk, and Race in American Medicine,” Laura Specker Sullivan makes the compelling case that trust is essential to buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Studies have demonstrated that community forums that provide accurate, linguistically- and culturally-appropriate information to its participants offer a potential approach for enhancing trust [34] , [50] . Second, increased education and sensitivity training in medical mistrust for healthcare providers and medical researchers may help facilitate a constructive dialogue about how to acknowledge mistrust, recognize implicit and explicit biases, and begin to foster or deepen trust across relationships with patients and community members [51] , [52] . Addressing this challenge head on will be an integral action for transforming the culture and atmosphere of mistrust in medical institutions that has been reported by racial and ethnic minorities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that community forums that provide accurate, linguistically- and culturally-appropriate information to its participants offer a potential approach for enhancing trust [34] , [50] . Second, increased education and sensitivity training in medical mistrust for healthcare providers and medical researchers may help facilitate a constructive dialogue about how to acknowledge mistrust, recognize implicit and explicit biases, and begin to foster or deepen trust across relationships with patients and community members [51] , [52] . Addressing this challenge head on will be an integral action for transforming the culture and atmosphere of mistrust in medical institutions that has been reported by racial and ethnic minorities.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of PLWH interviewed in this study had positive interactions within the healthcare system and during COVID-19 testing, yet a significant proportion of participants expressed concerns that they could not trust the test results. Medical mistrust has been described as a social determinant of health and is considered to be a result of historic and ongoing structural injustices that disproportionately impact Black patients, with downstream health impacts [ 30 , 31 ], including for HIV [ 32 , 33 ]. Mistrust has been seen throughout the United States during the COVID-19 pandemic due to misinformation and politicization of the COVID-19 response [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…With reference to trust in medical institutions, Larson et al (44) emphasize the importance of past experiences. Relatedly, the current tendency toward lack of trust in science and medicine has been related to historical and contemporary structures of inequality and injustice (40,82), i.e., to historical or personal experiences of being deprioritized or maltreated by institutions, including healthcare (83). History offers several examples of negative effects of contraceptive methods and their methods of administration, which have initially gone unrecognized by medical authorities (51)(52)(53)(54)(55)(56)(57)61).…”
Section: The Use and Perceived Reliability Of Informationmentioning
confidence: 99%